2015
DOI: 10.1007/s10585-015-9748-8
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of asymptomatic brain metastases from renal cell carcinoma

Abstract: Current guidelines for metastatic renal cell carcinoma (mRCC) do not recommend routine brain imaging as part of the surveillance protocol unless central nervous system (CNS) symptoms or abnormal laboratory values suggest brain involvement. We hypothesized that strict adherence to these guidelines will delay diagnosis and management of RCC brain metastases. Retrospective review of our IRB-approved kidney cancer database examined a consecutive series of subjects from 1995 to 2012. We identified all mRCC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
3
22
0
1
Order By: Relevance
“…Hence, they advocated that early asymptomatic BM diagnosis and early radiation or neurosurgical intervention might improve OS. 13 On the contrary, Choi et al did not recommend routine evaluation for BM, because their study did not show OS difference between synchronous and metachronous BM. 10 In the present study, earlier detection of BM did not improve the survival or rate of unrecovered neurological symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, they advocated that early asymptomatic BM diagnosis and early radiation or neurosurgical intervention might improve OS. 13 On the contrary, Choi et al did not recommend routine evaluation for BM, because their study did not show OS difference between synchronous and metachronous BM. 10 In the present study, earlier detection of BM did not improve the survival or rate of unrecovered neurological symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that 50% of advanced melanoma patients developed BM and 10% of metastatic lesions presented as an intraparenchymal hemorrhage [26]. With respect to renal cell carcinoma, it was estimated that BM occurred in 2-16% of patients and that when BM emerged late in illness, renal cell carcinoma was refractory to other therapies [27]. BM is an unusual event for patients with aggressive lymphoma [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines pertaining to metastatic RCC do not recommend routine brain imaging for surveillance purposes unless there are concurrent CNS symptoms or other abnormalities indicating brain involvement (19). Patients with a history of tobacco abuse and pulmonary metastases are more likely to have metastasis to the brain; therefore, this may serve as an indication for surveillance imaging of the brain (19).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a history of tobacco abuse and pulmonary metastases are more likely to have metastasis to the brain; therefore, this may serve as an indication for surveillance imaging of the brain (19). With increasing understanding of the role of angiogenic dysregulation in the pathogenesis of RCC, novel therapeutic strategies are utilizing targeted anti-angiogenic agents with varying degrees of success (20).…”
Section: Discussionmentioning
confidence: 99%